Hepatic carcinoma expressing inhibin: case report of a proposed novel entity and review of the literature - Antonia Syrnioti; Evangelia Athanasiou; Prodromos Hytiroglou (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Hepatic carcinoma expressing inhibin is a recently described neoplasm with varied architecture, including trabecular, pseudoglandular, follicular/microcystic, organoid, solid and tubular patterns of growth. We report a case of hepatic carcinoma expressing inhibin that occurred in a 47-year-old woman presenting with epigastric and back pain. The tumor was located in the left hepatic lobe and measured 12 cm in diameter. On immunohistochemical stains, the neoplastic cells were positive for inhibin, as well as cytokeratins 7, 8/18 and 19. There was mild focal expression of synaptophysin, and lack of expression of hepatocytic markers. The histogenesis of hepatic carcinoma expressing inhibin is presently uncertain. From a practical point of view, this neoplasm can potentially cause diagnostic pitfalls by simulating other primary or metastatic tumors, such as hepatocellular carcinoma, cholangiocarcinoma, neuroendocrine tumors, and follicular carcinoma of thyroid gland. Performing inhibin immunostain could assist in the differential diagnosis of liver tumors with unusual histologic features.